Admissions due to vaccine preventable diseases in a large paediatric intensive care unit in Greece over a 10‐year period. (1st September 2021) - Kazantzi, Maria; Prapa, Marilena; Christakou, Eleni; Paraschou, Dimitra; Kalabalikis, Panagiotis; Barbaressou, Charikleia; Papaevangelou, Vassiliki
Abstract : Aim: Childhood immunisation is an important preventive measure. However, care givers may delay routine immunisations or seek exemptions from state vaccine mandates. Vaccine refusal creates barriers on vaccine coverage and leads to morbidity and mortality. Methods: Our study reviews morbidity and mortality from vaccine preventable diseases (VPDs) in a large paediatric intensive care unit in Greece over a 10‐year period. Results: During the study period, 73 cases of VPDs were recorded, corresponding to 3.5% of total paediatric intensive care unit admissions. Influenza was the most prevalent VPD, followed by pneumococcal disease, measles, pertussis and meningococcal disease. Most patients (83.3%) were unvaccinated for the admission's VPD. Outcome was unfavourable for 31.9% of the patients (17 children died, 6 developed chronic impairment). Conclusion: Absent or incomplete vaccination may result in serious morbidity and mortality from preventable diseases. Strengthening vaccination strategies are needed to improve individual protection as well as herd immunity.